2022
DOI: 10.1007/s00222-022-01168-z
|View full text |Cite
|
Sign up to set email alerts
|

Critical exponents for a percolation model on transient graphs

Abstract: We consider the bond percolation problem on a transient weighted graph induced by the excursion sets of the Gaussian free field on the corresponding cable system. Owing to the continuity of this setup and the strong Markov property of the field on the one hand, and the links with potential theory for the associated diffusion on the other, we rigorously determine the behavior of various key quantities related to the (near-)critical regime for this model. In particular, our results apply in case the base graph i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In the last decade, it has been subject to intensive research after a non‐trivial percolation phase transition has been identified for this model on double-struckZd$\mathbb {Z}^d$ in [27], see for instance [2, 9, 12, 29]. Only very recently, in the remarkable paper [15], it has been shown that this phase transition is sharp, and, rather amazingly, the critical exponents have been identified for a related model of the level‐set percolation on the cable system of double-struckZd$\mathbb {Z}^d$ in [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, it has been subject to intensive research after a non‐trivial percolation phase transition has been identified for this model on double-struckZd$\mathbb {Z}^d$ in [27], see for instance [2, 9, 12, 29]. Only very recently, in the remarkable paper [15], it has been shown that this phase transition is sharp, and, rather amazingly, the critical exponents have been identified for a related model of the level‐set percolation on the cable system of double-struckZd$\mathbb {Z}^d$ in [13].…”
Section: Introductionmentioning
confidence: 99%
“…Consumers who purchase products publish their usage experiences on the www.ijacsa.thesai.org internet, and over time, their word-of-mouth (WoM) accumulates or decreases, leading to the diffusion of product information. This diffusion effect affects the number of consumers attracted during the normal sales phase [15][16]. The diffusion model of Base is shown in Fig.…”
mentioning
confidence: 99%